A theorical approach to the fundamentals of unrest in capital-labor relationships - Paula Abal Medina; Universidad Nacional de San Martín (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2014)
The purpose of this article is to conduct a bibliographical review around the notion of labor unrest. As a starting point, we assume that the delivery of actual work by the workforce is a difficult process that takes place in business settings. Which are the ways in which this is guaranteed to happen? Which are the most significant fields of affection? Two bibliographic core sources, which we termed "the standpoints of power and unrest", and "the debates about autonomy and workforce self-management", make substantial contributions. Starting from a synthesis of the previous criticism, we provide arguments that support the notion of three fields that affect the relationship between capital and labor: Time, subjectivity, and the collective as a way of being.